Measurement hysteresis of touch-trigger probes for CNC machine tools. (May 2020) - Woźniak, Adam; Męczyńska, Katarzyna
Highlights: Hysteresis phenomenon of probes for CNC machine tools is analyzed theoretically. Hysteresis parameters are proposed for its description and quantification. Theoretical model of hysteresis has been verified using a specially designed set-up. The occurrence of the hysteresis of probes for CNC machine tools is confirmed. Abstract: Touch-trigger probes for CNC machine tools are widely used for workpiece setup and, potentially, for dimensional inspection. Up to now, the probe measurement hysteresis has not been considered. In this paper, the hysteresis phenomenon is analysed using a specially designed set-up and parameters are proposed for its description and quantification. The new apparatus is based on an actuated hollow master artefact which does not require the machine axes to move. Exemplary results for different probe technologies are presented.